DUKUNGAN INFORMASIONAL BERHUBUNGAN DENGAN STIGMA HIV PADA PEREMPUAN POSITIF HIV - Joula Timisela (Poltekkes Kemenkes Maluku, 2018)
HIV/AIDS has become a global pandemic and has received serious attention because it is growingrapidly in the world including Indonesia. Increased HIV in women because women are vulnerable toHIV transmission. Various impacts can be experienced by women when contracting HIV, such as thepresence of HIV Stigma. Women are very vulnerable to HIV stigma and the consequences are due togender inequality. Women are often blamed for causing HIV infection and being immoral by thecommunity. Informational support’s necessary to HIV positive women facing HIV stigma. The studyaimed to identify the relationship between informational support and stigma of HIV in HIV positivewomen. The study used cross-sectional analytic design. The sample were 106 HIV-positive women,aged 15-60 years. The informational support assessment used questionnaires MOS-SS that have beenmodified, while the assessment of the stigma of HIV used the short version of the questionnaire BergerStigma Scale Indonesian translation. The results of the analysis showed that there is a relationshipbetween informational support and stigma of HIV (p-value 0,0001 α: 0.05) with OR 13,65. This studyconcludes that informational support is significantly related to HIV stigma, and one of therecommended interventions to reduce HIV stigma. Keywords: Informational support, HIV stigma, HIV positive women